Perkembangan Teknologi Pakan Ikan Otomatis dalam Perikanan Modern : Tinjauan Literatur - Putri, Diana Eka (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2023)
The development of technology in the era of the industrial revolution 4.0 is currently increasingly sophisticated, with its rapid progress making it easier for humans to do their work. One of the advances in current technology is its ability to run a tool automatically. Automation also plays an important role in the field of fish farming, where businesses are challenged to innovate in the face of the industrial revolution. The concept of modern fish farming involves automatic feeding based on a predetermined time. This allows fish farm owners to feed regularly and consistently. The research method used is a systematic literature review, by collecting data from the Google Scholar database. By using the keywords ("Automatic Fish Feed" AND "IoT"), 402 articles were obtained and then selected to get 20 articles that are relevant to the topic taken for analysis. This literature study provides an in-depth understanding of the trends and challenges in the development of IoT-based automatic fish feed devices. This article provides an overview of the development of automated fish feed. It can be concluded that automated fish feed uses one of the microcontrollers such as Arduino Uno or Arduino Nano, NodeMCU ESP8266, and Wemos D1R1 or Wemos D1 mini. Overall, the researchers have made an automatic fish feed with time accuracy that is in accordance with what has been set before.